Experience of Point-of-Care Devices in Obstetrical Care - Karlsson, Ove (Seminars in Thrombosis and Hemostasis, 2017)
During pregnancy and puerperium, there are pronounced hemostatic changes characterized by increased coagulability and decreased fibrinolysis. In addition, hemostasis can change dramatically during obstetric complications. Several reports have described substandard management of hemostatic defects in this setting and state the need for guidelines and better care. Point-of-care devices can assess hemostatic status and are especially suitable in perioperative settings. Using point-of-care devices, no time is required for transportation, allowing faster availability of results and providing potential for better care of the patient. This article will demonstrate the use of a viscoelastic method in six different patients; five with impaired hemostasis, and where the use of viscoelastic method contributes or should have contributed to better care. The cases represent patients with normal delivery; postpartum hemorrhage (PPH); PPH with low fibrinogen; placental abruption; preeclampsia with hemolysis, elevated liver enzymes, low platelet count syndrome; and finally, one patient with sepsis. This article also shows the need for good practices and good supervision to implement the devices in patient care.
Keywords: obstetric; point-of-care; viscoelastic method; thromboelastography; thromboelastometry; hemostatic complication; postpartum hemorrhage; DIC; fibrinogen